Comparison of acalabrutinib plus obinutuzumab, ibrutinib plus obinutuzumab and venetoclax plus obinutuzumab for untreated CLL: a network meta-analysis - Sheng, Zhixin; Song, Shilei; Yu, Miao; Zhu, Hongguang; Gao, Anran; Gao, Weijie; Ran, Xuehong; Huo, Da (Leukemia & lymphoma, 2020)
The optimal chemotherapy-free regimens for treatment-naive CLL still remains undefined. We searched relevant published reports. Three trials with 1017 subjects were identified. In the network meta-analysis, acalabrutinib plus obinutuzumab (Aca + Obi) improved PFS than ibrutinib plus obinutuzumab (Ibu + Obi) (HR:0.43, p = .02) and venetoclax plus obinutuzumab (Ven + Obi) (HR:0.30, p < .001) as IRC assessment. Sensitivity analysis of investigator assessment also showed improved PFS with Aca + Obi than Ibu + Obi (HR:0.46, p = .04) and Ven + Obi (HR:0.34, p = .002). Among these first-line treatments (Aca + Obi, Ibu + Obi, Ven + Obi and chlorambucil plus obinutuzumab (Chl + Obi)), Aca + Obi regimen had the highest probability of 99.1% (IRC assessment) or 98.0% (investigator assessment) to reach the longest PFS. The survival advantage with Aca + Obi was not statistically significant, compared to Ibu + Obi (HR:0.51, p = .21) and Ven + Obi (HR:0.38, p = .07). No significant difference was found in AEs analysis. Our data indicated that Aca + Obi seemed to prolong the PFS than Ibu + Obi and Ven + Obi. Considering our limits, prospective clinical trials directly comparing these regimens are warranted.